Renal vein and inferior vena cava thrombosis as a rare complication of pyelonephritis - Wirth, Jan; Houdek, Karel; Moláček, Jiří; Bednář, Lukáš (Journal of vascular surgery cases and innovative techniques, 2025)
Renal vein thrombosis (RVT) and inferior vena cava thrombosis are extremely rare conditions, yet potentially life-threatening complications of pyelonephritis. This report describes the case of a 66-year-old patient with undiagnosed pyelonephritis, who subsequently developed RVT with an extension to the inferior vena cava. The management of the condition involved a multidisciplinary approach that resulted in nephrectomy with an extraction of the thrombus through cavotomy. This case report emphasizes the necessity of early recognition of RVT owing to pyelonephritis and complex management of this condition to prevent the adverse outcomes of impending complications.
Keywords: Renal vein thrombosis; Cavotomy; Acute pyelonephritis; Thromboinflammation; Nephrectomy